1988
DOI: 10.1111/j.1464-410x.1988.tb05087.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Value of Antibiotics and Catheter Care in the Prevention of Urinary Tract Infection after Transurethral Prostatic Resection

Abstract: One hundred patients were prospectively randomised into two groups to receive either a single dose of 1 g ampicillin and 80 mg gentamicin pre-operatively or no antibiotic prophylaxis. The incidence of breakage in the continuity of the closed drainage system was documented. All patients with urinary tract infection (UTI), catheterisation, clinical prostatic carcinoma, neurogenic bladder and bladder tumours were excluded. UTIs, bacteraemia and fever were noted. There were 7 late exclusions. The incidence of UTI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
0
14
1
5
Order By: Relevance
“…The prospective nature of this study, the 1–month duration of the postoperative follow–up and the small number of patients lost to follow–up probably increased the sensitivity of determination of the incidence of PBU. The incidence of PBU detected on removal of the catheter in our study (8%) was similar to that reported in the literature [2, 8]. In contrast, the incidence of PBU between postoperative days 7 and 10 (14%) was higher than usually reported during this period [1, 2, 3, 6, 8].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The prospective nature of this study, the 1–month duration of the postoperative follow–up and the small number of patients lost to follow–up probably increased the sensitivity of determination of the incidence of PBU. The incidence of PBU detected on removal of the catheter in our study (8%) was similar to that reported in the literature [2, 8]. In contrast, the incidence of PBU between postoperative days 7 and 10 (14%) was higher than usually reported during this period [1, 2, 3, 6, 8].…”
Section: Discussioncontrasting
confidence: 46%
“…Disconnection of the closed drainage system constitutes a major risk factor for bacteriuria in medical patients with short–term catheterization [20]. Several studies have demonstrated a direct correlation between disconnection of the system and bacteriuria [8]. Our study shows, for the first time, that disconnection of the closed urine drainage system is the most important risk factor for PBU after TURP.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…6,[18][19][20][21][22][23][24][25] This is further supported by a RCT demonstrating equivalent outcomes with the use of levofloxacin versus TMP-SMX as antibiotic prophylaxis for TURP. 2 As such, the wide variety of antibiotic regimens used by urologists at our institution is understandable as no single agent stands out as superior with respect to efficacy (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…4 Clinical efficacy was shown for antibiotic classes including fluoroquionolones, third generation cephalosporins, aminoglycosides and trimethroprim-sulfamethoxazole (TMP-SMX). [18][19][20][21][22][23][24][25] Based on the available evidence, the 2008 American Urology Association (AUA) Best Practice Statements (BPS) on Urologic Surgery Antimicrobial Prophylaxis recommends use of prophylactic antibiotics for all patients undergoing TURP. 1 The recommended first-line agents are fluoroquinolones or TMP-SMX, with alternatives including aminoglycosides alone or with ampicillin, cephalosporins or amoxicillin/clavulanate <24 hours prior to TURP.…”
Section: Introductionmentioning
confidence: 99%